Kingdom of Lesotho : Technical Assistance Report-Government Finance Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
In response to a request from the authorities and as part of the United Kingdom's Department for International Development (DFID) Enhanced Data Dissemination Initiative (EDDI) 2 project, a government finance statistics (GFS) mission visited Maseru, Lesotho, during January 20-31, 2020. The mission was the last, in a series of five consecutive technical assistance (TA) missions to Lesotho, as part of the EDDI 2 project. The objective of the five-year project, that started in 2015 was to foster compilation and dissemination of GFS and public sector debt statistics (PSDS) consistent with international methodological standards. The work program under the project identified the enhancement of classification of transactions in fiscal accounts and the expansion of the institutional coverage of data to include all significant general government units as key milestones to achieve by the end of the project.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet